2001
DOI: 10.1172/jci10559
|View full text |Cite
|
Sign up to set email alerts
|

Delayed wound repair and impaired angiogenesis in mice lacking syndecan-4

Abstract: Frank Echtermeyer and Michael Streit contributed equally to this work.Received for publication June 12, 2000, and accepted in revised form December 8, 2000.The syndecans make up a family of transmembrane heparan sulfate proteoglycans that act as coreceptors with integrins and growth factor tyrosine kinase receptors. Syndecan-4 is upregulated in skin dermis after wounding, and, in cultured fibroblasts adherent to the ECM protein fibronectin, this proteoglycan signals cooperatively with β 1 integrins. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
366
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(393 citation statements)
references
References 23 publications
21
366
0
3
Order By: Relevance
“…Initially, animals were anesthetized in a gas chamber containing 5% isoflurane and 95% oxygen where after the animals were intubated and ventilated with 2% isoflurane and 98% oxygen. Aortic banding (AB) was performed on eight week old male C57BL/6JBomTac mice (wild-type (WT); N=20) and syndecan-4 -/-mice [12] on a C57Bl/6J background (N=20) by placing a ligature distally around the ascending aorta as previously described [11]. Sham-operated animals underwent the same procedure without tightening the suture around the aorta.…”
Section: Mouse Model Of Pressure Overloadmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, animals were anesthetized in a gas chamber containing 5% isoflurane and 95% oxygen where after the animals were intubated and ventilated with 2% isoflurane and 98% oxygen. Aortic banding (AB) was performed on eight week old male C57BL/6JBomTac mice (wild-type (WT); N=20) and syndecan-4 -/-mice [12] on a C57Bl/6J background (N=20) by placing a ligature distally around the ascending aorta as previously described [11]. Sham-operated animals underwent the same procedure without tightening the suture around the aorta.…”
Section: Mouse Model Of Pressure Overloadmentioning
confidence: 99%
“…These interactions are important for the assembly of focal adhesions, cell attachment and spreading [9]. Whereas, expression of syndecan-4 has been shown to be increased in the hypertrophic myocardium of mice after myocardial infarction [10] and in human aortic stenosis [11], lack of syndecan-4 in mice has been shown to disturb and delay wound healing [12]. Hence, syndecan-4 is a good candidate for being a mechanosensor in cardiac fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced neural crest cell motility (Breau et al, 2006) β3 integrin Integrins Total Defects in platelet aggregation and clot retraction, hemmorhages, postnatal anemia, and reduced survival (Hodivala-Dilke, 1999) β8 integrin Integrins Total Embryonic or perinatal lethality with profound defects in vascular development, insufficient vascularization of the placenta and yolk sac (Zhu et al, 2002) VCAM-1 Integrins Total Embrynic lethality at E10-12, abnormal placental development (Gurtner et al, 1995) Syndecan-4 Extracellular matrix Total Blood vessel defects in the placenta; defects in angiogenesis and wound repair (Echtermeyer, 2001;Ishiguro, 2000;Kojima, 2002) N-syndecan Extracellular matrix Total Impaired neural migration in the developing brain (Hienola et al, 2006) Perlecan Extracellular matrix Total Defects in heart integrity, invasion of brain tissue into the overlaying ectoderm, severe defect in cartilage, cleft palates and death shortly after birth from respiratory failure. (Costell et al, 1999) Tenascin C Extracellular matrix Total NC cells fail to disperse laterally (Tucker, 2001) Laminin γ1 Extracellular matrix Total Death at E5.5, lack of basement membranes (Smyth et al, 1999) Laminin β2 Extracellular matrix Total Postnatal death between P15-30, neuromuscular junctions and glomerular defects (Noakes et al, 1995a;Noakes et al, 1995b;Patton et al, 1997) Laminin α2 Extracellular matrix Total Death by 5 weeks postnatal, severe muscular dystrophy and peripheral neurophathy (Miyagoe et al, 1997) Laminin α2 (dy/dy) Extracellular matrix Spontaneous Adult lethality, severe muscular dystrophy and peripheral nerve dysmyelination (Patton et al, 1999;Patton et al, 1997) Laminin α3 Extracellular matrix Total Death at P2-3, epithelial adhesion defect (Ryan et al, 1999) Laminin α4 Extracellular matrix Total Transient microvascular defect with hemorrhages and misalignment of neuromuscular junctions (Patton et al, 2001;Thyboll et al, 2002) Laminin α5 Extracellular matrix Total Death at E14-E17, with placental vessel, neural (Miner et al, 1998;Miner and Li, 2000) Protein Function Type Phenotype Reference tube, limb, and kidney defects Fibronectin Extracellular matrix Total Death before E14.5, shortened anterior-posterior axes, deformed neural tubes, and defects in mesodermally derived tissues.…”
Section: Note On Nomenclaturementioning
confidence: 99%
“…Female BALB/cByJ and C57BL/6 mice (both 6-8 weeks of age) were obtained from the Elevage Janvier Laboratory (Le Genest St Isle, France). SDC4 À / À mice (backcrossed for 10 generations on C57BL/6 mice) 13 were kindly provided by Sarah Wilcox-Adelman (Boston Biomedical Research Institute, Boston, USA). All animal experiments were performed according to institutional and state guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…SDC4 expression is often involved in migration and adhesion of various cells including DCs [9][10][11] . Previous animal studies have shown a pivotal role for SDC4 in protecting against kidney injury 12 , limiting endotoxin shock 7 and promoting wound healing 13 . However, an inhibition of SDC4 by a specific antibody protected mice from cartilage damage in a murine model of osteoarthritis 14 .…”
mentioning
confidence: 99%